Basic psychological needs and life satisfaction: behavioral genetic analysis - Bratko, Denis (2013)
Basic psychological needs have been shown to correlate phenotypically with life satisfaction and to predict life satisfaction over and beyond personality dimensions. Since it has been shown that correlations between personality dimensions and life satisfaction are completely due to overlapping genetic effects, the goal of this study was to test whether basic psychological needs and life satisfaction share a common genetic structure. Data was collected via mail from 338 twin pairs (36 MZM, 49 DZM, 69 MZF, 70 DZF, 114 DZO), aged between 15 and 22 years (M=18.6, SD=2.31). All participants filled in Ryan and Deci’s Basic Psychological Needs Scale and Pavot and Diener’s Satisfaction with Life Scale. Basic psychological needs correlated in the .42-.47 range with life-satisfaction. Broad sense heritability of basic psychological needs was in the .50-.60 range, while for life satisfaction it was .75. Cholesky decomposition was used to analyze the relationship between basic needs and life satisfaction. Results supported that heritable differences in life satisfaction were entirely accounted for by the genetic architecture of basic psychological needs. There was also a small, but significant effect of overlapping non-shared environmental influences with need for relatedness.